Theories of the information society - Webster, Frank (London : Routledge, 2002)
"Popular opinion suggests that information has become a distinguishing feature of the modern world. Where once economies were built on industry and conquest, we are now instead said to be part of a global information economy. In the first edition of Theories of the Information Society Frank Webster set out to make sense of the information explosion, taking a sceptical look at what thinkers mean when they refer to the information society, and critically examining all the major post-war theories and approaches to informational development. In this new and thoroughly revised edition the author brings his study right up to date both with new theoretical work and with social and technological changes - such as the rapid growth of the Internet and accelerated globalisation - and reassesses the work of key theorists in light of these changes."
"This book will be essential reading for students of contemporary social theory and anybody interested in social and technological change in the post-war era."--BOOK JACKET.
1. Introduction -- 2. Information and the Idea of an Information Society -- 3. The Information Society as Post-Industrialism: Daniel Bell -- 4. Information, Restructuring and Globalization -- 5. Information Capitalism: Manuel Castells -- 6. Information and Advanced Capitalism: Herbert Schiller -- 7. Information Management and Manipulation: Jurgen Habermas and the Decline of the Public Sphere -- 8. Information Reflexivity and Surveillance: Anthony Giddens -- 9. Information and Postmodernism and Postmodernity-- 10. Conclusion : is there an Information Society?
Includes bibliographical references and index.
English.
Keywords: Communication -- Social aspects; Communication -- Technological innovations; Information society; Information technology; Information policy